(untitled) (CIPEEX, 2025)
Introduction: obesity induces various respiratory adaptations to maintain an efficient level of gas exchange and tissue oxygenation. The reduction of thoracic mobility, decreased diaphragm excursion, and lower capacity for forced expiratory maneuvers are some of the factors of obesity that impact pulmonary function. Objective: to relate the presence of obesity with pulmonary function in workers in the industrial sector. Methods: This is a cross-sectional observational study conducted with 143 workers from the industrial sector, with 94 (67.5%) being male and 49 (34.3%) female. Obesity was assessed by body mass index (BMI) and waist circumference (WC). Lung function was assessed by spirometry. Results: Workers with a higher BMI showed a longer forced expiratory time (FET) (∆= +0.54s, p=0.006), and those with a smaller waist circumference performed better in spirometric variables, with a lower forced vital capacity (FVC) (∆= +0.43L, p=0.019), %FVC (∆= +12.2%, p<0.001), and percentage of predicted forced expiratory volume in one second (%FEV1) (∆= +7.3%, p=0.044). FVC (∆= +0.43L, p=0.019), %FVC (∆= +12.2%, p<0.001), and the predicted percentage of forced expiratory volume in the first second (%FEV1) (∆= +7.3%, p=0.044). There was a positive correlation of BMI (r=0.17, p=0.042) and WC (r=0.31, p<0.001) with FEV1. CC showed a negative correlation with %FEV1 (r=0.21, p=0.014). Conclusion: The pulmonary function parameters indicated different results according to BMI and WC. It is important to emphasize the significance of encouraging the maintenance of CC within the expected values, as it can affect lung function and is a highly related marker for cardiovascular diseases.